Accounting for mitigation of N-fertiliser emissions at national and project scales - Stirling, Clare M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
This report provides an overview of the United Nations Framework Convention on Climate Change (UNFCCC) reporting process for national greenhouse gas (GHG) inventories with particular focus on the methodology used for estimating direct nitrous oxide (N2O) emissions from mineral fertiliser. Examples are given of several schemes for sub-national or project- level approaches to monitor and estimate the impact of fertiliser best management practice (BMP) on direct N2O emission reductions. The extent to which these approaches align with those of the national inventory is evaluated and conclusions drawn on actions needed to close any gaps. Collectively, 63% of world fertiliser consumed is reported at the higher Tier 2 and Tier 3 levels. However, countries reporting at the Tier 1 level for direct N2O emissions from fertilisers still predominate, accounting for 180 of the total 191 reporting countries. Case studies of fertiliser BMP were generally found to align well with national inventory methods, mainly through the use of modifiers to Tier 1 & 2 emission factors (EFs). Good quality activity data (AD) is a main challenge to full alignment of project and national inventory-based estimates of fertiliser-induced emissions and emission reductions. Lack of quality AD also limits the extent to which national inventories can capture mitigation impacts. Given the early stage of developing accounting processes for agricultural GHGs, an opportunity now exists to design national GHG inventory processes to reflect emissions savings achieved through mitigation actions such as implementing fertiliser BMPs. To achieve this, it is necessary to strengthen the alignment among different policy instruments, inventory compilation processes and national data providers. In this respect, we should seize opportunities made available from instruments such as the Nationally Determined Contributions that would support development of project-specific, nationally consistent and inventory-aligned measurement, reporting and verification (MRV) methods for capturing mitigation actions, including the establishment of robust baseline AD.